N-Heterocyclic carbene-catalyzed michael-michael-lactonization cascade for the enantioselective synthesis of tricyclic delta-lactones - Mukherjee, Subrata; Ghosh, Arghya; Marelli, Udaya Kiran; Biju, Akkattu T. (Organic Letters, 2018)
Enantioselective synthesis of tricyclic delta-lactones with three contiguous stereocenters has been demonstrated by the N-heterocyclic carbene (NHC)-catalyzed functionalization of benzylic C(sp(3))-H bonds. The NHC-catalyzed reaction of enals with dinitrotoluene derivatives under oxidative conditions proceeds via the chiral alpha,beta-unsaturated acylazoliums and produces the delta-lactones in good yields and excellent diastereoselectivity and enantioselectivity. This mild and atom-economic cascade reaction takes place in a Michael/Michael/lactonization sequence and tolerates a broad range of functional groups.